SPAWNING CONCENTRATIONS OF THE SARDINE, SARDINELLA GIBBOSA (BLEEKER), OFF THE NORTH ANDHRA COAST IN MARCH - APRIL 1969 - Sekharan, K V; Muthu, M S; Rao, G Sudha; Rao, B Narayana (Indian Journal of Fisheries, 2011)
Adult Sardinella gibbosa in pre-spawning and spawning stages were observed inMarch 1969 in Waltair - Kakinada region from catches made 15-20 km from shore.Plankton collections made during this period off Kakinada contained eggs which have beenassigned to S. gibbosa based on circumstantial evidence and resemblances. Most of thestomachs of 5. ^/'66oM examined during the period were either empty or contained verylittle food. These indicate that there was extensive spawning of the species off theNorth Andhra coast in March-April 1969.